Phytochemical and chemotaxonomic study on Fallopia dentatoalata (Fr. Schm.) Holub. (October 2021) - Meng, Lin; Qi, Wen; Zhang, Xuan; Zhang, Dong; Huang, Yourong; Shi, Ming; Li, Hongyu
Abstract: Phytochemical study of Fallopia dentatoalata gave seventeen compounds, two sterols (8 and 10 ), three anthraquinones (5, 16 and 17 ), one chromone (13 ), two stilbenes (3 and 4 ), two amides (11 and 12 ), six flavonoids (1, 2, 6, 7, 14 and 15 ) and one fatty acid (9 ). Their structures were elucidated by spectroscopic methods and in comparison with the reported data. Compound 11 was obtained from genus Fallopia for the first time, and all of the compounds were firstly isolated from F. dentatoalata . The chemotaxonomic significance of these compounds was also discussed, which demonstrated the relationships between F. dentatoalata and some other species of genus Fallopia . Highlights: We studied the chemical constituents of Fallopia dentatoalata. All compounds were isolated from this plant for the first time. Fallopia dentatoalata may have close relationships with other species of Fallopia.